PENGARUH MOTIVASI DAN KEPUASAN KERJA TERHADAP KINERJA DOSEN PASCASARJANA PERGURUAN TINGGI SWASTA DI PALEMBANG - Iin Hendrayani (Fakultas Ekonomi Universitas Tridinanti Palembang, 2016)
This study aims to: (a) analyze the influence of work motivation to the lectures performance, (b) analyze the influence of job satisfaction to lecturers performance, (c) analyze simultaneously the influence between work motivation, job satisfaction to the performance of the lecturer. This study was conducted to tenured lecturers of Private Colleges Graduate in Palembang. The population in the study were 94 respondents from 8 graduate faculty of Private college Masters in Palembang. The research sample using saturated sample technique but the questionnaire is returned only 73 of 7 Graduate faculty of private college. Test of data validity used validity and reliability. Test of requirements analysis used multicollinearity test, heteroscedasticity test, normality test, and linierity test. Data analisys Technique used descriptive analysis, and multiple linier regression. The calculations used SPSS for windows. The results of the research was value of Fcount (37 693)> Ftable (3,127) and it can be seen that the significance of 0.000 is less than 0.005 This meant that the independent variables of motivation and job satisfaction simultaneously have a significant influence to the lecturers performance of the Graduate faculty of private college in Palembang. Partially tcount motivation variable (4.834)> t table (1.994) and it is known that the significance of 0.000 is less than 0.005 means that the null hypothesis is rejected, the conclusion that motivation (X1) has positive effect to the lecturers (Y) Of Graduate faculty of private college in Palembang . Tcount job satisfaction variable (3.384)> t table (1.994) and it showed that the significance of 0.000 is less than 0.005 means the null hypotesis is rejected, the conclusion that Job Satisfaction (X2) has positive effect to the lecturers performance (Y) Graduate faculty of private college.In this study concluded that motivation and job satisfaction lecturer has positive and significant effect to the performance of the Graduate faculty of private college in Palembang. Keywords: Motivation, Job Satisfaction, Performance